Aplicação do modelo de tutoria em tarefas de leitura e escrita para criança com dislexia do desenvolvimento - Machado, Andréa Carla; Capellini, Simone Aparecida [UNESP] (My University, 2014)
Developmental dyslexia is characterized by impairment in reading and writing as a result of changes in the cognitive-linguistic behavior. The goal of the research was to analyze and compare the performance on tasks of reading and writing in children with developmental dyslexia after a mentoring program. Participated in this study 15 children of both genders from 3rd to 7th grade public schools of a city in the State of São Paulo, with average age (M = 9.4) and (DP = 1.08) divided into GIexperimental group (7 children who received intervention) and GII – control group (8 children did not receive the intervention, they were matched according to sex and age group with GI). The children were subjected to the diagnostic survey of reading and writing and to the intervention program in Reading Recovery tutoring. The data regarding reading and writing tasks related to mentoring program were collected in CEES-Centro de Estudos de Educação e Saúde da UNESP. The results revealed statistically significant difference between the GI and GII, where children with dyslexia in the GI showed superior performance on the task of reading words and reading the book I in relation to children of the GII. It was concluded that the GI introduced significant advances compared to GII that did not receive mentoring intervention, demonstrating that due to variability of cognitive-linguistic profile of children with dyslexia, it is necessary to develop, mainly, in the school context programs with specific difficulties that focus on interventions of this population.

A dislexia do desenvolvimento é caracterizada pelo prejuízo em leitura e escrita decorrentes de alterações no comportamento cognitivo-linguístico. O objetivo da pesquisa foi analisar e comparar o desempenho em tarefas de leitura e escrita em crianças com dislexia do desenvolvimento após um programa de tutoria. Participaram deste estudo quinze crianças de ambos os gêneros de 3º ao 7º ano de escolas públicas de uma cidade do interior do Estado de São Paulo, com média de idades (M= 9,4) e (DP=1,08) divididos em GI – grupo experimental (7 crianças que receberam intervenção) e GII – grupo controle (8 crianças não receberam a intervenção, os mesmos foram pareados segundo sexo e faixa etária com o GI). As crianças foram submetidas ao levantamento diagnóstico de Leitura e Escrita e ao programa de intervenção em tutoria Reading Recovery. Os dados referentes às tarefas de leitura e escrita vinculadas ao programa de tutoria foram coletados no CEES – Centro de Estudos de Educação e Saúde da UNESP – campus de Marília- SP. Os resultados revelaram diferença estatisticamente significativa entre o GI e o GII, onde as crianças com dislexia do GI apresentaram desempenho superior na tarefa de leitura de palavras e leitura do livro I em relação às crianças do GII. Concluiu-se que o GI apresentou avanços significativos comparados à GII que não recebeu intervenção de tutoria, demonstrando que devido à variabilidade do perfil cognitivo-linguístico das crianças com dislexia, é necessário que se desenvolva, principalmente, no contexto escolar programas com intervenções centradas nas dificuldades especificas dessa população.
Application of model of tutoring in reading and writing tasks for children with developmental dyslexia
Keywords: crianças; Dislexia; Escrita; Leitura; Tutoria